Translation, Cross-Cultural Adaptation, and Validation of the Traditional Chinese Version of the VISA-P Questionnaire. - Syu, Fang-Yu; Lin, Yin-Liang; Chien, Andy; Chen, Chao-Ying; Hsieh, Benjamin Yung-Thing; Shih, Yi-Fen (Orthopaedic Journal of Sports Medicine, 2024)
Background: The Victorian Institute of Sport Assessment-Patella (VISA-P) questionnaire is a widely accepted instrument for measuring the severity of symptoms and pain in patients having sustained patellar tendinopathy. Purpose: To adapt the VISA-P questionnaire cross-culturally to a traditional Chinese version (VISA-P-Ch) and validate its psychometric properties. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: The VISA-P questionnaire was adapted to a traditional Chinese version following international recommended guidelines, including translation, synthesis, back translation, revision by expert committee, pretesting, and validation. The psychometric properties were tested in 15 healthy controls and 15 participants with patellar tendinopathy. Face validity was judged by the authors and participants. Known-groups validity was tested by comparing the VISA-P-Ch scores between symptomatic and asymptomatic participants using an independent t test. Concurrent validity was determined by comparing the Blazina classification of the participants against VISA-P-Ch scores using the Spearman correlation coefficient. Test-retest reliability was assessed by calculating the intraclass correlation coefficient (ICC) following a 24- to 48-hour interval. Internal consistency was determined by the Cronbach alpha. Results: The expert committee and participants reported good face validity of the VISA-P-Ch. Significantly higher scores were found in the control group than in the patellar tendinopathy group (98.47 ± 3.04 vs 65 ± 11.9; P <.001). Concurrent validity showed a high correlation between VISA-P-Ch and the Blazina classification system (r = -0.899; P <.01). The test-retest reliability was excellent (ICC = 0.964). Internal consistency was found to be good for both the first and second assessments (Cronbach α = 0.834 and 0.851). Conclusion: The VISA-P-Ch was proven to be a reliable and valid questionnaire with similar psychometric properties as the original VISA-P.